Respuesta :

Answer:

[tex] \dfrac{(x - 2)^2}{(x - 1)^2} [/tex]

Step-by-step explanation:

[tex] \dfrac{x^2 + x - 6}{x^2 - 6x + 5} \div \dfrac{x^2 + 2x - 3}{x^2 - 7x + 10} = [/tex]

[tex] = \dfrac{x^2 + x - 6}{x^2 - 6x + 5} \times \dfrac{x^2 - 7x + 10}{x^2 + 2x - 3} [/tex]

[tex] = \dfrac{(x + 3)(x - 2)}{(x - 1)(x - 5)} \times \dfrac{(x - 5)(x - 2)}{(x - 1)(x + 3)} [/tex]

[tex] = \dfrac{(x + 3)(x - 2)(x - 5)(x - 2)}{(x - 1)(x - 5)(x - 1)(x + 3)} [/tex]

[tex] = \dfrac{(x - 2)(x - 2)}{(x - 1)(x - 1)} [/tex]

[tex] = \dfrac{(x - 2)^2}{(x - 1)^2} [/tex]

ACCESS MORE